Physical therapy of children with particular systemic lesion based on the undifferentiated connective tissue dysplasia - Yuliia Rudenko; Oleksandr Zviriaka; Yuliia Arieshyna (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to develop and prove the effectiveness of a comprehensive physical therapy program for children with systemic visual and musculoskeletal lesions based on the undifferentiated connective tissue dysplasia. Material and methods: the study involved 24 children of 6 years old. The study was conducted at the special educational complex. Research methods: medical histories review; clinical examination by the criteria of T. Milkovsky-Dimitrov and A. Karkashov; definition of the joint hypermobility degree by the Carter-Wilkinson criteria in the modification of Beiton; assessment of the back extensor muscles' and abdominal press' strength endurance (by A.M. Reisman and F.I. Bagrov tests); visometry. Results: During a preliminary study a tendency of an increase in the joint hypermobility degree in accordance with the myopia degree was established: children with mild myopia had mild form of joint hypermobility; children with moderate myopia had mild and moderate degrees of joint hypermobility; joint hypermobility at children with a high degree of myopia varied from mild to severe (generalized). A tendency of an increase in the number of children with impaired posture in accordance with an increase in the myopia degree was also established. A comprehensive physical therapy program was developed and implemented. It included modern technologies and recovery tools: therapeutic exercises for the eye muscles (solarization, palming); musculosceletal system training on the BOSU platform; balanced daily diet; self-massage of the circular eye muscles and eyelids; art therapy (fairy tale therapy); Su-Jok therapy. This methods made up the essence of the author's program named «Sleepy Kittens». This program affected the visual analyzer and the musculoskeletal system positively. Conclusions: As a result of physical therapy measures in the main group, a number of children with high degree of myopia decreased; strength endurance of the back extensor muscles and abdominals increased; a number of children with joint hypermobility of moderate degree decreased; joint hypermobility of high degree was absent.